Perancangan Website Sistem Informasi Tagihan Pembayaran Perusahaan Daerah Air Minum: (Studi Kasus Badan Usaha Milik Desa XYZ) - Restuyadi, Andrian Rizky; Saeppani, Asep; Sofiyan, Yanyan (Jurnal Informatika, Multimedia dan Teknik, 2024)
In the digital era, efficiency and easy access to public services are crucial. The Regional Drinking Water Company (PDAM) must adapt to technological advancements to improve service quality. A major challenge is the manual and inefficient management of billing and payments, leading to service time inefficiency. This study aims to enhance operational efficiency and service quality at PDAM by designing a bill payment information system website. Data was collected through interviews, observations, and literature studies to understand system requirements. The website was developed using the prototype method, allowing continuous adjustments and evaluations until the system meets PDAM's operational needs. The final result is a website implemented at PDAM, providing easy access and efficiency in the bill payment process, increasing customer satisfaction, and supporting the digital transformation of public services.